FROM WORD TO IMAGE: THEOLOGY OF SEEING - Elavathingal, Sebastian (Asian Horizons, 2017)
This article is an attempt to show that “seeing” is a consummate theological experience and “images” are valid theological works. Images are generated in the matrix of worship (bhakti), which is essentially a creative experience, since it integrates knowledge (jñāna) and action (karma), mind and body, conception and perception. In Christian faith tradition, the Cross as the Tree of Life embodies and expresses the message of salvation in the most effective and exhaustive manner. “Seeing” the Cross as the Tree of Life can be an experience of theological “exclamation,” a wordless exultation.